The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1046/j.1365-2141.2001.03183.x
|View full text |Cite
|
Sign up to set email alerts
|

Early elevation of serum thrombopoietin levels and subsequent thrombocytosis in healthy preterm infants

Abstract: Summary. To verify pathophysiological mechanisms underlying thrombocytosis in low-birth-weight (LBW) preterm babies, we evaluated kinetic changes in platelet counts and thrombopoietic cytokines including thrombopoietin (TPO), interleukin 6 (IL-6) and IL-11 in 24 uncomplicated preterm infants. Platelet counts in cord blood (CB) (265^64 Â 10 9 /l) were similar to adult levels, increased by d 14 (473^140 Â 10 9 /l), and then remained fairly constant. Thrombocytosis (. 500 Â 10 9 /l) was observed in 9/24 (38%) sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 35 publications
(84 reference statements)
3
23
2
Order By: Relevance
“…We and other investigators recently documented that TPO contributes to thrombocytosis, together with IL-6, in patients with certain infections [17], Kawasaki disease [18], and in those having undergone surgery [19]. Furthermore, we found a link between early elevation of TPO and subsequent thrombocytosis in preterm infants [20]. Kapsoritakis et al [21]also indicated a significant elevation of serum TPO levels in patients with inflammatory bowel disease.…”
Section: Discussionsupporting
confidence: 51%
“…We and other investigators recently documented that TPO contributes to thrombocytosis, together with IL-6, in patients with certain infections [17], Kawasaki disease [18], and in those having undergone surgery [19]. Furthermore, we found a link between early elevation of TPO and subsequent thrombocytosis in preterm infants [20]. Kapsoritakis et al [21]also indicated a significant elevation of serum TPO levels in patients with inflammatory bowel disease.…”
Section: Discussionsupporting
confidence: 51%
“…2,22,[24][25][26][27] Sasanakul et al 25 noted a steady rise in the platelet counts of term infants during the first 7 to 14 postnatal days with subsequent counts remaining fairly constant over the next 2 weeks. Aballi et al 22 evaluated platelet counts of premature infants whose birth weights ranged from 750 to 2250 g and observed a steady rise in counts during the first 24 days.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that the mean platelet counts of premature infants with birth weights <2500 g increase steadily during the first 10 to 14 days of life then remain constant over the remainder of the neonatal period. 26,27 Obladen et al 24 determined that the platelet counts of 562 very low birth weight infants increased steadily during the first 6 weeks of life, with the most significant increase noted during the first 2 weeks. Saxonhouse et al 28 reported that reticulated platelet counts increase during the first 5 days following delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Recently, several studies have clarified the relationship between blood TPO level and platelet count in thrombocytopenic and non-thrombocytopenic non-DS neonates. [5][6][7][8][9][10][11][12] Accumulating evidence has shown that although neonates of all gestational ages produce endogenous TPO, their TPO response to thrombocytopenia may be suboptimal. 5,6 In contrast with extensive studies about thrombocytopenia in non-DS neonates, [5][6][7][8][9][10][11][12] little is known about underlying mechanisms including TPO contribution responsible for thrombocytopenia in DS newborns.…”
Section: Introductionmentioning
confidence: 99%